Autoimmune pulmonary alveolar proteinosis mimicking Mycoplasma pneumonia in an adolescent. (2020) - Meka, Shaiva Ginoya; Mohr, Madison; Nair, Girish Balachandran; Salman, Bassel A.
Abstract: Pulmonary alveolar proteinosis (PAP) is a rare disease of abnormal surfactant production and accumulation. It is typically divided into three main categories: autoimmune, secondary and genetic. The genetic type is more common in children and adolescents, while the autoimmune type is most commonly seen in adults. Here we present an unusual case of autoimmune PAP presenting in an adolescent by mimicking findings of Mycoplasma pneumonia. Although both PAP and Mycoplasma pneumonia may reveal the same findings of the "crazy paving pattern" on computed tomography imaging, it is imperative to distinguish the two as treatment options are dissimilar. Highlights: Consider pulmonary alveolar proteinosis in adolescents with "crazy paving" pattern on imaging. Delayed diagnosis due to infectious mimickers is common in the young age group. Autoimmune pulmonary alveolar proteinosis requires timely diagnosis.